2019
DOI: 10.1016/j.seppur.2019.05.057
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic separation and characterization of vivianite from digested sewage sludge

Abstract: To prevent eutrophication of surface water, phosphate needs to be removed from sewage. Iron (Fe) dosing is commonly used to achieve this goal either as the main strategy or in support of biological removal. Vivianite (Fe(II) 3 (PO 4 ) 2 *8H 2 O) plays a crucial role in capturing the phosphate, and if enough iron is present in the sludge after anaerobic digestion, 70 to 90% of total phosphorus (P) can be bound in vivianite. Based on its paramagnetism and inspired by technologies used in the mining industry, a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(63 citation statements)
references
References 26 publications
5
57
0
Order By: Relevance
“…The reason for the change in vivianite crystal morphology was possibly due to Fe 2+ adsorbed onto the surface of sponge iron and IHO through static electricity, hydrogen bonding, chemical bonding and hydrophobicity (Rothe et al, 2016). Moreover, because sponge iron itself had strong magnetic properties, the vivianite produced with sponge iron as a seed crystal was also magnetic and could be easily adsorbed by neodymium magnet, and then be separated from the sludge (Prot et al, 2019). Fig.5 shows the crystal size of different seed crystals.…”
Section: Variations Of Vfamentioning
confidence: 99%
“…The reason for the change in vivianite crystal morphology was possibly due to Fe 2+ adsorbed onto the surface of sponge iron and IHO through static electricity, hydrogen bonding, chemical bonding and hydrophobicity (Rothe et al, 2016). Moreover, because sponge iron itself had strong magnetic properties, the vivianite produced with sponge iron as a seed crystal was also magnetic and could be easily adsorbed by neodymium magnet, and then be separated from the sludge (Prot et al, 2019). Fig.5 shows the crystal size of different seed crystals.…”
Section: Variations Of Vfamentioning
confidence: 99%
“…The mass efficiency of process designs can be assessed with the results of the mass and energy balances conducted in step 3. For example, if two different processes recover P but process (A) integrates struvite crystallization [96] while process (B) integrates the magnetic extraction of vivianite [97], it is useful to assess the recovery rate of the influent P of each process. Furthermore, if resource recovery technologies include not only the extraction but also on-site refinement of a recovered product, KPIs originally developed for the chemical or pharmaceutical process assessment could be applied to assess the performance of a particular recovery technology in comparison to an alternative one.…”
Section: Technical Process Assessment (Gate Ii)mentioning
confidence: 99%
“…The additional treatment step leads on the one hand to additional operational costs for energy consumption [44], maintenance costs to prevent membrane fouling [104], and waste management costs for retentate handling [105]; on the other hand, it may generate steady economic benefits in the form of revenues from water customers [106]. Furthermore, P recovery requires additional investment costs but may also lead to lower waste management costs due to improved sludge dewaterability and benefits from recovered product marketing [97].…”
Section: Technical Process Assessment (Gate Ii)mentioning
confidence: 99%
“…Due to the magnetic properties of vivianite, this opens up opportunities for its targeted recovery from the sludge via magnetic separation. This approach has recently gained significant interest and has shown significant economic and practical potential (Prot et al, 2019).…”
Section: Fe-p-s Interactions During Wastewater Treatment In System-wimentioning
confidence: 99%
“…This requires the understanding of Al and P interactions and characterization of Al-P mineral precipitates in WWTP, which would facilitate in P recovery using appropriate separation techniques. In this context, Prot et al (2019) reported P can be recovered using magnetic separation process from digested sludge, rich in Fe-P mineral precipitates (e.g. vivianite).…”
Section: Effects Of Al-sludge Dosing On Sewage Characteristicsmentioning
confidence: 99%